Pengaruh Jarak Tanam terhadap Pertumbuhan dan Produksi Jagung (Zea Mays L) Non Hibrida di Lahan Balai Agro Teknologi Terpadu (ATP) - Kartika, Trimin (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2018)
The research entitled: The Effect of Planting Distance on Growth and Production of Non Hybrid Maize (Zea Mays L) in the Land of Integrated Technology Agro Center (ATP)